(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2021)
The purpose of this research was to determine the effect of Saanen doe goats’ birth types on milk yields, lactation length, dry period, days open and kidding interval at PT Fajar Taurus. This research employed a case study method using secondary data of production and reproduction of Saanen doe goats. Data was analysed using Microsoft Excel program and Kruskal Wallis test. The results showed percentages of Saanen doe goats with single, twinning and triplets birth are 47.94%, 39.73% and 12.33% respectively. Milk yields for single birth was 1,14±0,43 litres/goat/day, lactation length of 286.43±119.73 days, dry period of 68.89±18.57 days, days open of 205.31±117.67 days, and kidding interval of 355.31±117.67 days. Milk yields for twinning birth was 1.32±0.49 litres/goat/day, lactation length of 270±219.43 days, dry period of 69.10±17.52 days, days open of 189.10±227.22 days, and kidding interval of 339.10±227.22 days. Meanwhile, milk yields for triplets birth was 0.93±0.40 litres/goat/day, lactation length of 360±228.97 days, dry period of 66.67±23.78 days, days open of 276.67±240.38 days, and kidding interval of 426.67±240.38 days. There is nonsignificant effect of birth types on milk yields, lactation length, days open and kidding interval in Saanen doe goats (P>0.05). However, birth types were found to have a significant effect on dry period (P<0.05).